Relationship between rumen bacterial community and milk fat in dairy cows - Si, Boxue; Liu, Kaizhen; Huang, Guoxin; Chen, Meiqing; Yang, Jiyong; Wu, Xufang; Li, Ning; Tang, Wenhao; Zhao, Shengguo; Zheng, Nan; Zhang, Yangdong; Wang, Jiaqi (Frontiers in Microbiology, 2023)
Milk fat is the most variable nutrient in milk, and recent studies have shown that rumen bacteria are closely related to milk fat. However, there is limited research on the relationship between rumen bacteria and milk fatty. In this experiment, forty-five healthy Holstein dairy cows with alike physiological and productive conditions were selected from medium-sized dairy farms and raised under the same feeding and management conditions. The experimental period was two weeks. During the experiment, raw milk and rumen fluid were collected, and milk components were determined. In this study, 8 high milk fat percentage (HF) dairy cows and 8 low milk fat percentage (LF) dairy cows were selected for analysis. Results showed that the milk fat percentage in HF group was significantly greater than that of the dairy cows in the LF group. 16S rRNA gene sequencing showed that the rumen bacterial abundance of HF dairy cows was significantly higher than that in LF dairy cows; at the genus level, the bacterial abundances of Prevotellaceae_UCG-001, Candidatus_Saccharimonas, Prevotellaceae_UCG-003, Ruminococcus_1, Lachnospiraceae_XPB1014_group, Lachnospiraceae_AC2044_group, probable_genus_10 and U29-B03 in HF group were significantly higher than those in the LF group. Spearman rank correlation analysis indicated that milk fat percentage was positively related to Prevotellaceae_UCG-001, Candidatus_Saccharimonas, Prevotellaceae_UCG-003, Ruminococcus_1, Lachnospiraceae_XPB1014_group, Lachnospiraceae_AC2044_group, probable_genus_10 and U29-B03. Furthermore, Prevotellaceae_UCG-001 was positively related to C14:0 iso, C15:0 iso, C18:0, Ruminococcus_1 with C18:1 t9, Lachnospiraceae_AC2044_group with C18:1 t9 and C18:1 t11, U29-B03 with C15:0 iso. To sum up, rumen bacteria in dairy cows are related to the variation of milk fat, and some rumen bacteria have potential effects on the deposition of certain fatty acids in raw milk.